2020
DOI: 10.1590/s0102-865020200050000007
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of wound healing effect of alginate film containing Aloe vera gel and cross-linked with zinc chloride

Abstract: Purpose To develop a new wound dressing composed of alginate and Aloe vera gel and cross-linked with zinc ions. Methods The aloe-alginate film was characterized using scanning electron microscopy (SEM), swelling profile, mechanical properties, polysaccharide content and X-ray diffraction (XRD). Thirty Wistar rats were divided in two groups a) treated with aloe-alginate film and b) control (treated with sterile gauze). Wound contraction measurements and hystological anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 29 publications
0
16
1
3
Order By: Relevance
“…Aloe vera yang dibuat dalam sediaan lembaran memiliki sifat fleksibel dan elastis sehingga membuat wound healing sheet mudah digunakan dan tidak menimbulkan rasa sakit ketika dipasang atau dilepas. 15 Tekstur sediaan lembaran antara pemberian ekstrak 50% dan 100% berbeda. Wound healing sheet ekstrak 50% memiliki tekstur yang lebih lembut sedangkan ekstrak 100% lebih kasar.…”
Section: Pembahasanunclassified
See 2 more Smart Citations
“…Aloe vera yang dibuat dalam sediaan lembaran memiliki sifat fleksibel dan elastis sehingga membuat wound healing sheet mudah digunakan dan tidak menimbulkan rasa sakit ketika dipasang atau dilepas. 15 Tekstur sediaan lembaran antara pemberian ekstrak 50% dan 100% berbeda. Wound healing sheet ekstrak 50% memiliki tekstur yang lebih lembut sedangkan ekstrak 100% lebih kasar.…”
Section: Pembahasanunclassified
“…yang meneliti efek dari aloe-alginate film cross-linked with zinc chloride sebagai wound dressing bisa memodulasi fase inflamasi, meningkatkan angiogenesis pada fase proliferatif dan meningkatkan kolagen tipe I dan ini dipengaruhi oleh senyawa yang terkandung dalam Aloe vera. 15 Penelitian yang sama yang dilakukan oleh Paques dkk. menyimpulkan bahwa aloe-alginate film cross-linked with calcium memiliki efek yang lebih besar dalam modulasi fase inflamasi dan kolagenesis dibandingkan dengan alginat tanpa gel Aloe vera.…”
Section: Pembahasanunclassified
See 1 more Smart Citation
“…Due to its high biocompatibility and non-irritating properties, AV is often used in combination with MPs to develop wound dressings. Many studies have shown that MPs wound dressings incorporating AV enhance scar inhibition by promoting wound contraction and orderly deposition of collagen [58,275,342]. Other natural agents also have been shown to enhance collagen repair, reduce collagen deposition and accelerate healing by impeding the growth of gelatinous scar tissue, such as heparin, essential oils, silk etc.…”
Section: Development Of Activities-enhanced Mps Wound Dressingsmentioning
confidence: 99%
“…Because of its hydrophilic nature, alginate is capable to take multiple forms [ 11 , 12 , 13 , 14 ] (beads, blends, dressings, electrospun scaffolds, flexible fibers, films, foams, gels, hydrogels, injections, microparticles, microspheres, nanoparticles, polyelectrolyte complex, powders, ropes, sheets, sponges) that could be applied on post-traumatic wounds or exuding wounds (ulcers) while decreasing contamination [ 15 , 16 , 17 , 18 ], either as a stand-alone biomaterial, or in various combinations.…”
Section: Introductionmentioning
confidence: 99%